Comparing the accuracy of estimating soil moisture using the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI) - Dwi Priyo Ariyanto; Abdul Aziz; Komariah Komariah; Sumani Sumani; Magarsa Abara (Universitas Sebelas Maret, 2020)
The Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI) are used to monitor and identify different types of drought, including meteorological, hydrological, and agricultural droughts. This study evaluates the accuracy of estimating soil moisture levels using the two indexes. The analysis correlated the SPI and the SPEI over three years (November 2016–October 2019) using Rstudio, with average monthly soil moisture taken using a Soil Moisture Sensor; 3-, 6- and 12-months SPI and SPEI showed a positive correlation for soil moisture (Sig <0.05), whereas 1-month SPI and SPEI results did not. A regression test was used to get an equation model for estimating soil moisture content. The correlation for soil moisture between the 1-month SPI and SPEI results was insignificant (p-value >0.05). In contrast, the 3-, 6-, and 12-months indexes were significant (p-value <0.05). Estimating soil moisture content using the SPEI (50–59.09%) had a higher accuracy value than the SPI (36.36%), which indicates the SPEI can more reliably predict soil moisture.